PELAKSANAAN MANAJEMEN SARANA PRASARANA DALAM PENINGKATAN MUTU PENDIDIKAN DI SD NEGERI 011 PEKAN TUA KECAMATAN KEMPAS KABUPATEN INDRAGIRI HILIR - RIAU - jurnalmap map (MAP (Jurnal Manajemen dan Administrasi Publik), 2022)
The purpose of the study was to describe the implementation of infrastructure management in improving the quality of education in SD Negeri 011 Pekan Tua, Kempas District, Indragiri Hilir Regency, Riau. This research is a field research, using a qualitative approach. The results of the study found that the implementation of infrastructure management in improving the quality of education in SD Negeri 011 Pekan Tua, Kempas District, Indragiri Hilir Regency, Riau was carried out by means of Infrastructure Planning (Planning), namely school coordination meetings, determining school programs, and determining the need for educational infrastructure. Organizing Infrastructure (Organizing) includes setting the organizational structure of infrastructure management, division of work tasks / job descriptions. Implementation of Infrastructure Facilities (Actuating) in the form of procurement, maintenance and elimination of infrastructure facilities. Infrastructure Controlling is carried out by taking an inventory.